2019
DOI: 10.5194/acp-2019-587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Light absorption properties of aerosols over Southern West Africa

Abstract: <p><strong>Abstract.</strong> Southern West Africa (SWA) is an African pollution hotspot but a relatively poorly sampled region of the world. We present an overview of <i>in-situ</i> aerosol optical measurements collected over SWA in June and July 2016 as part as the DACCIWA (Dynamics–Aerosol–Chemistry–Clouds Interactions in West Africa) airborne campaign. The aircraft sampled a wide range of air mas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…consistent with this picture of aged haze having a reduced BrC contribution compared to freshly emitted aerosol. Other recent studies have also shown AAE close to 1 in African biomass burning smoke that had been aged for several days (Zuidema et al, 2018;Denjean et al, 2019). These optical properties are also in a similar range to measurements by Saturno et al (2018), who measured smoke from southern Africa once it had reached Amazonia after 10 days transport.…”
Section: Physical and Optical Properties Of Highly Aged Biomass Burnisupporting
confidence: 83%
“…consistent with this picture of aged haze having a reduced BrC contribution compared to freshly emitted aerosol. Other recent studies have also shown AAE close to 1 in African biomass burning smoke that had been aged for several days (Zuidema et al, 2018;Denjean et al, 2019). These optical properties are also in a similar range to measurements by Saturno et al (2018), who measured smoke from southern Africa once it had reached Amazonia after 10 days transport.…”
Section: Physical and Optical Properties Of Highly Aged Biomass Burnisupporting
confidence: 83%
“…pro- 445 posed that the CL derived from the ultraclean upper tropospheric air.In the vicinity of the western African coast, similar tropospheric stratification has been observed in a recent aircraft campaign. Aerosol and trace gas profile measurements over the Gulf of Guinea in July 2016, measured under the influence of aged BB plumes originating in central Africa, revealed two distinct aerosol layers, where the upper one, centered at 3.8 km altitude, was enriched in rBC (~0.3 µg m -3 ), CO 450 (~340 ppb), and OA (~65 µg m -3 )(Denjean et al, 2019; Flamant et al, 2018). Moreover,Weinzierl et al (2011) reported fvol = 26 % (13 -52 %, p3 -p97) for BB plumes near the western African coast in 2008 during SAMUM-2, which are larger than the fvol within the UPL in this study.…”
mentioning
confidence: 99%
“…In the vicinity of the western African coast, similar tropospheric stratification was observed in a recent aircraft campaign. Aerosol and trace gas profile measurements over the Gulf of Guinea in July 2016, measured under the influence of aged BB plumes originating in central Africa, revealed two distinct aerosol layers, where the upper one, centered at 3.8 km altitude, was enriched in rBC (∼ 0.3 µg m −3 ), CO (∼ 340 ppb), and organics (∼ 65 µg m −3 ) (Denjean et al, 2019;Flamant et al, 2018). Moreover, Weinzierl et al (2011) reported f vol = 26 % (13 %-52 %, p 3 -p 97 ) for BB plumes near the western African coast in 2008 during SAMUM-2, which are larger than the f vol within the UPL in this study.…”
Section: Offshore Aerosol Particle and Trace Gas Profilesmentioning
confidence: 99%